Improvement of English Speaking Ability In 7th Grade Students of Ganesha Junior High School Denpasar Through TANDUR Method - Hartomi Arya Franata, I Putu; Simpen, I Wayan; Dhanawaty, Ni Made (e-Journal of Linguistics; Vol 14 No 2 (2020): e-jl July, 2020)
This study aims to determine the application of the TANDUR method can improve speaking skills in learning English. This research is a qualitative study using five types of methods which include tests, TANDUR experiments, questionnaires, interviews, and observations. The results of the questionnaire answered by students showed the factors that influence their motivation in the learning process. The factors that influence students in the learning process are divided into two, namely internal factors and external factors. Based on the results of the study, it can be concluded that the ability of students in speaking English increases after the application of the TANDUR method. Three aspects of speech assessed in this study, were grammar, vocabulary, and understanding that experienced an increase, both in class 7.1 which is the treatment class and class 7.3 which is the control class.